Internet and Religious Identity Construction: Jurus Sehat Rasulullah (JSR) Da’i (Preacher) Zaidul Akbar - Saipudin Ikhwan; Mahmud Hibatul Wafi (Jurnal Dakwah Risalah, 2021)
The presence of the internet has influenced the way people interact with their social environment, including in the context of religion. Internet seems to eliminate boundaries, space and time in social interactions. This led to a fundamental change in how a person’s identity was formed. This study discusses how online interactions can shape one’s religious identity. “Jurus Sehat Rasulullah” as a da'wah theme which encourages Muslims to maintain their health and perform Islamic medicine is analyzed textually. This qualitative research in collecting data using online observation by observing JSR and its users. The search was focused on the Instagram account @ZaidulAkbar. The results showed that there was a religious identity construction process through the exchange of symbols among internet users who followed the official account of “Jurus Sehat Rasulullah.”